A favorable lifestyle lowers the risk of coronary artery disease consistently across strata of non-modifiable risk factors in a population-based cohort - Kristian Dimovski; Marju Orho-Melander; Isabel Drake (BMC, 2019)
Abstract Background A healthy lifestyle has been shown to reduce the risk of coronary artery disease (CAD). The extent to which lifestyle influences the risk of CAD for people with pre-existing non-modifiable risk factors is less studied. We therefore examined the associations between a favorable lifestyle and incidence of CAD in population subgroups based on gender, age, educational level, and parental history of myocardial infarction. Methods A total of 26,323 men and women from the Malmö Diet and Cancer study were prospectively followed-up for 18 years. A favorable lifestyle was determined using a four-component lifestyle score based on data collected at baseline: no smoking, no obesity, regular physical activity, and a healthy diet. Cox proportional hazards regression models were used to estimate the relative risk of CAD during follow-up and cumulative risk during a 10-year interval. Results A favorable lifestyle was associated with a 44% (95% confidence interval, 38-48%) lower risk of CAD compared to an unfavorable lifestyle. The relative risk was similarly reduced among subjects subdivided by gender, age group, educational level, and parental history of myocardial infarction. These findings corresponded with a reduced standardized 10-year incidence of CAD of around 40% in each subgroup. Conclusion In this population-based cohort, a favorable lifestyle was associated with a significant reduction of CAD across strata of non-modifiable risk factors. These findings provide support for lifestyle modification as a means for risk reduction in a range of subgroups within a general healthy population.